Steam Coil Air Heater (SCAH) Modelling as Porous Medium to Analyze Flow Characteristic and Reduce Self Energy Usage in Gresik Unit 1 Steam Power Plant - Eko Ariyanto; Wawan Aries Widodo (IPTEK The Journal for Technology and Science, 2019)
This study deals with flow and heat transfer characteristic in a Heat Exchanger if its tube modules completely or partially dismantled. The heat exchanger is a Steam Coil Air Heater (SCAH) Installed in Gresik unit 1 Steam Turbine Power Plant. Nowadays the power plant operate mostly utilized natural gas as a fuel. When it utilized natural gas SCAH are not give benefit and only give flow resistance for combustion air flow. This study use numerical simulation model with commercial Computational Fluid Dynamic (CFD) software. The simulation on 3D model with steady state flow condition. The model use energy model, Heat Exchanger Model, realizable k-Epsilon for turbulence viscous model and SCAH model as Porous Medium (PM). Modelling SCAH as a PM will avoid time consuming mesh generation and simulations with high CPU usage. Fives scenarios of tube module dismantling simulated in 100% load. This study result both quantitative and qualitative data coresspond with flow and heat transfer characteristic. The model with original scenarios give good result in terms of pressure and outlet temperature with commisioning data. The contour data results show there are several secondary flow due to enlargement of flow area. Numerical results of variation S1,S2,S3,S4 are indicated decreasing total pressure drop about 32.27%, 51.29%, 47.04%, 65.25% respectively. And temperature rise for each schenario will decrease to 29.29% (S1), 46.51% (S2) , 47.92% (S3), 68.28% (S4) respectively,except for S5 have no pressure drop and temperature rise since all module are dismantled.